2020
DOI: 10.1158/1055-9965.epi-20-0865
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Lung Cancer Screening and Detection

Abstract: Lung cancer is the leading worldwide cause of cancer mortality, as it is often detected at an advanced stage. Since 2011, low-dose CT scan-based screening has promised a 20% reduction in lung cancer mortality. However, effectiveness of screening has been limited by eligibility only for a high-risk population of heavy smokers and a large number of false positives generated by CT. Biomarkers have tremendous potential to improve early detection of lung cancer by refining lung cancer risk, stratifying positive CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…The hypothetical biomarker of early lung cancer could be detected in the blood, which is a particularly valuable source of molecular information on disease-related processes, with many actual and prospective applications as a “liquid biopsy” of cancer. For over a decade, intensive studies to identify new biomarkers of early lung cancer were focused on various components of the blood, including circulating tumor cells (CTC), circulating free DNA (cfDNA), autoantibodies, and components of the proteome, peptidome, and transcriptome of serum/plasma [ 9 , 10 , 11 , 12 ]. Moreover, cancer-related metabolites present in the blood appeared as an emerging source of biomarkers for the detection and diagnosis of different malignancies [ 13 ], including lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothetical biomarker of early lung cancer could be detected in the blood, which is a particularly valuable source of molecular information on disease-related processes, with many actual and prospective applications as a “liquid biopsy” of cancer. For over a decade, intensive studies to identify new biomarkers of early lung cancer were focused on various components of the blood, including circulating tumor cells (CTC), circulating free DNA (cfDNA), autoantibodies, and components of the proteome, peptidome, and transcriptome of serum/plasma [ 9 , 10 , 11 , 12 ]. Moreover, cancer-related metabolites present in the blood appeared as an emerging source of biomarkers for the detection and diagnosis of different malignancies [ 13 ], including lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Potential biomarkers for early lung cancer can be found in various biological fluids; however, blood is the richest and most readily available source [ 10 , 11 ]. Candidates for such biomarkers include serum proteins, free nucleic acids, and metabolites [ 11 , 12 ]. Several works reported serum/plasma proteins, which levels are associated with the risk of lung cancer [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, serum metabolites and lipids have emerged as another class of potential biomarkers in lung cancer [ 16 , 17 ]. Several other review papers could be suggested that cover this well-researched field [ 11 , 12 , 13 , 18 , 19 , 20 , 21 ]. However, though numerous biomarker candidates have been proposed only a few of them have been positively validated in the proper clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Blood is the most widely available source of biomarkers potentially enhancing the power of early lung cancer detection or discrimination of lung nodules. Several components of blood, including circulating tumor cells, circulating tumor DNA, microRNA, autoantibodies, and specific serum/plasma proteins, have been analyzed in the search for such biomarkers [ 7 , 8 , 9 , 10 ], but none have been widely adopted in clinics yet. Moreover, serum metabolome represents a novel potential source of cancer markers, and a few large studies revealed sets of metabolites whose serum/plasma levels discriminated lung cancer patients from matched controls [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%